The red horseman - Coonts, Stephen (New York : Pocket Books, 1994)
When the Soviet Union collapses, thousands of nuclear warheads go unaccounted for, and it'll take someone of Jake Grafton's talents to make sure they don't end up in the wrong hands. With the USSR on the brink of dissolution, a vast nuclear arsenal is suddenly ripe for the taking by mercenaries, rogue nations, and insane Russian nationalists. Grafton must stop them, and he may have to do it alone.
Keywords: Nuclear weapons plants -- Fiction; Terrorism -- Fiction; Action and adventure fiction